Strengthening Professional Learning Communities Through Policy and Institutional Support in Diverse Educational Contexts - Rizqi, Putri Umrotur; Syafika, Wanda (Sinergi International Journal of Education, 2024)
This narrative review explores the role of Professional Learning Communities (PLCs) in enhancing teacher competencies across various educational settings. The study aims to synthesize empirical evidence on the effectiveness of PLCs in promoting professional development and improving instructional practices. Literature was collected from databases such as Scopus, ERIC, and Google Scholar using keywords including "Professional Learning Community," "teacher competency development," and "collaborative learning." Articles published within the last ten years were reviewed, with inclusion criteria focused on peer-reviewed studies addressing teacher development in PLC contexts. Findings indicate that PLCs significantly improve reflective teaching, collaborative lesson planning, and formative assessment practices. Teachers engaged in PLCs report higher confidence and demonstrate more adaptive and student-centered pedagogies. Institutional support, leadership, and policy alignment emerge as critical enablers of PLC success. However, systemic challenges—including funding constraints, inconsistent policies, and insufficient training—limit their effectiveness, especially in low-resource contexts. The discussion highlights evidence-based strategies such as integrating PLCs into national education frameworks, investing in continuous training, and leveraging technology for virtual collaboration. The review concludes by emphasizing the need for context-sensitive implementation and further research on teacher experiences within PLCs. These insights can inform policy and practice aimed at fostering inclusive and sustainable professional learning cultures in education.